RZYMSKIE IGRZYSKA I HISZPAŃSKA CORRIDA. RYS PORÓWNAWCZY OBU TRADYCJI NA WYBRANYCH PRZYKŁADACH - Barbarzak, Dawid (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The text compares Roman ludi (mainly venationes), with Spanish tauromachy. Although there is no continuous tradition there are some universal similarities in their elements. We illustrate this by means of three comparisons: between the symbolical space of bullrings and amphiteatres, between the glory of gladiators and toreros as well as its influence on the world art, and finally between the ancient and contemporary controversies that led to a change or decline in both traditions.